2016
DOI: 10.5296/jse.v6i4.10011
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cooperative Learning Techniques on Intermediate Iranian EFL Learners' Reading Comprehension and Reading Strategies

Abstract: The purpose of this study was to investigate the effect of Cooperative Learning techniques on Intermediate Iranian EFL learners' reading comprehension, and reading strategies. In order to do this 90 Iranian EFL learners took, Preliminary English Test (PET), at the start for the researcher homogenize them regarding their general English proficiency. After that, 60 learners whose scores were one standard deviation above and below the mean were selected and were divided into 2groups; Experimental, and Control. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Finally, the results of the last research question of the study that was concerned with the effects of CSR on meta-cognitive awareness of EFL learners showed that CSR was conducive to higher levels of metacognitive awareness among EFL learners while engaged in reading. Similar to our results, other researchers have shown in the previous literature that CSR can have positive effects on improving EFL learners' metacognitive awareness (Benlyazid, 2019;Boardman et al, 2015;Gurk & Mall-Amiri, 2016;Vaughn et al, 2011). More specifically, our results are supported by Gurk and Mall-Amiri (2016), who claim that CSR can create multiple opportunities for EFL learners to socially construct meaning, interact in the target language, and accelerate their reading development.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, the results of the last research question of the study that was concerned with the effects of CSR on meta-cognitive awareness of EFL learners showed that CSR was conducive to higher levels of metacognitive awareness among EFL learners while engaged in reading. Similar to our results, other researchers have shown in the previous literature that CSR can have positive effects on improving EFL learners' metacognitive awareness (Benlyazid, 2019;Boardman et al, 2015;Gurk & Mall-Amiri, 2016;Vaughn et al, 2011). More specifically, our results are supported by Gurk and Mall-Amiri (2016), who claim that CSR can create multiple opportunities for EFL learners to socially construct meaning, interact in the target language, and accelerate their reading development.…”
Section: Discussionsupporting
confidence: 92%
“…The development of a learner's language competency is significantly influenced by strategies (Gurk, 2016). Learning strategies are described as those behaviors that support the acquisition, comprehension, or subsequent transfer of knowledge and abilities, or as the various combinations of activities students utilize during the learning process, with increased variety over time (Menéndez et al, 2018).…”
Section: Literature Review Learning Language Strategiesmentioning
confidence: 99%
“…Cooperative learning approaches have their roots in the communicative approaches, constructivist ideas, and traditional group work that were covered in earlier sections. But compared to traditional group work, cooperative learning has a clearer structure, is far more intentional, and pushes students intellectually and socially in a variety of ways (Gurk, 2016). According to Johnson and Johnson (1998), the reason they began researching cooperative learning and developing cooperative learning frameworks is that this method drastically alters the environment in classrooms.…”
Section: Cooperative Learningmentioning
confidence: 99%
“…All students get the opportunity to participate in classroom activities and thus achieve success using teamwork, which assists learners in enhancing their reading comprehension skills. Students get a chance to exercise language skills in cooperative learning (Gurk & Mall-Amiri, 2016).…”
Section: Introductionmentioning
confidence: 99%